How Europe can deliver. Optimising the division of competences among the EU and its member states (Gütersloh, 2017)
"The study was written in the context of Europe’s multiple crises. In the eyes of many voters, the performance of the EU has been disappointing in the aftermath of the economic and euro area debt crisis. The decision of the United Kingdom to leave the Union has drastically demonstrates this dissatisfaction. Against this background, the study aims to provide guidance for a better-performing EU through an improved division of competences between the European Union and its member states. The study shows were more integration would lead to a better provision of public goods and thereby to – hopefully - greater acceptance with the European citizens and where, in turn, member states would reach better results.